Comparative analysis of frequently used e-learning platforms - Jain, Shaily; Prabha, Chander; Nandan, Durgesh; Bhosale, Snehal (Frontiers in Education, 2024)
An online e-learning platform known as a learning management system (LMS) provides an interface between trainers, students, and administrators toward a common objective of learning. In the market, diverse LMSs with extensive functionalities are available to facilitate e-learning. In this article, we selected some popular LMSs majorly used by most schools and institutions for their teaching–learning process. We compared these LMSs in a discussion based on their technical specifications, technical features, administrative features, general features, and course management-related features. This comparative analysis could help users decide which LMS suits them best, according to their requirements. We also attempted to identify the limitations of these learning management systems so that users and organizations can determine which one is best suited to their needs.